Factors perceived by employees regarding their sick leave due to depression. Issue 6 (12th March 2016) - Corbière, Marc; Samson, Esther; Negrini, Alessia; St-Arnaud, Louise; Durand, Marie-José; Coutu, Marie-France; Sauvé, Geneviève; Lecomte, Tania
Abstract: Purpose : Depression is a leading factor of work disability throughout the world. However, a paucity of studies investigated factors related to the development of depression in the workplace prior to sick leave. This qualitative study aims to describe the factors related to the onset of depression at work prior to sick leave. Method : This study followed a descriptive interpretive design. Interviews were conducted with 22 individuals (15 women) who experienced depression while they were employed within an organization. The verbatim transcripts were coded using QDA-Miner software. Results : Participants ( n = 22) reported that their depression was partially or completely related to their work. From the analysis of all 22 participants' interviews transcripts, three major themes emerged: (1) work-related psychosocial risk factors (e.g. factors related to supervisors' attitudes and behaviors), (2) the individual's experience in employment (e.g. reactions to symptoms) and (3) the period preceding the sick leave of individuals who experienced depression (e.g. communication with the supervisor). Conclusions : These results support the importance of preventive intervention oriented toward decreasing psychosocial risks within organizations, and detecting workers at risk. Future studies should focus on factors that might influence individuals in their decision to reveal or not their difficulties to their supervisors. Implications for Rehabilitation: The conditions in which employees were working before they started their leave of absence should be identified; notably (1) relationships with organizational stakeholders (e.g. immediate supervisor, colleagues) and (2) psychosocial risk factors (e.g. work overload, over-commitment). A good relationship between the immediate supervisor and the employee is an important factor to prevent sick leave due to depression. The supervisors should be informed quickly after the first appearance of depressive symptoms in employees in order to implement feasible and appropriate accommodations as soon as possible.